Análise do programa de assistência estudantil sobre o rendimento escolar dos alunos do Instituto Federal do Ceará - Campus Fortaleza - Pinho, Antônio Sérgio Ribeiro (2017)
The Instituto Federal do Ceará - IFCE, Campus Fortaleza, is capable of impacting on the Academic Income Index (IRA) of the students, yet it is still capable of generating economic returns. To accomplish the task, the difference model was used to identify if the program promotes an increase in students' academic performance. To explain academic achievement, use a Dummy variable that indicates a student's participation in the program and a set of socioeconomic information of the students; They were collected from the IFCE - Campus Fortaleza and refer to the year 2012. In addition, the cash flow of the program was elaborated so that it was possible to construct the main financial measures of evaluation, which are NPV, IRR, cost / benefit and income Annualized, to subsidize the diagnosis of generation of economic return. The results highlight an influence of the student assistance program on school performance and also, because NPV is positive, benefit surpasses cost and an IRR is superior to Selic, it can be inferred that the program presents an economic return.